Isolation and characterization of psychrotrophic bacteria from refrigerated spoiled food - Somayeh Asadi Haris, 1984-; Shafinaz Shahir; Fakulti Biosains dan Kejuruteraan Perubatan (2013)
Thesis (Sarjana (Bioteknology)) - Universiti Teknologi Malaysia, 2013